Lições para a história das ciências no Brasil: Instituto Pasteur de São Paulo Lessons for the history of science in Brazil: São Paulo's Pasteur Institute - Maria Alice Rosa Ribeiro (História, Ciências, Saúde: Manguinhos)
Este artigo pretende mostrar a importância e o papel do Instituto Pasteur de São Paulo (1903-16) no desenvolvimento da ciência microbiológica no Brasil e no surgimento da indústria farmacêutica de capital nacional. The article highlights the role played by São Paulo's Pasteur Institute (1903-16) in the development of microbiological science in Brazil and in the emergence of a pharmaceutical industry owned by Brazilian capital.